1983
DOI: 10.21236/ada130348
|View full text |Cite
|
Sign up to set email alerts
|

Visual Fatigue in Sonar Control Rooms Lighted by Red, White, or Blue Illumination

Abstract: To determine, whether visual, fatigue, which can occur for some individuals working in red light at close distances, is a problem of importance for the operation of visual sonar displays. FINDINGS There was evidence that older, far-sighted individuals did show changes indicative of fatigue under red light while younger individuals with normal vision did not. No performance decrements were found for any group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
(11 reference statements)
1
8
0
Order By: Relevance
“…The findings indicated that the error scores under the red and blue illuminant were significantly higher than the error scores under white illuminant, a finding that was consistent with previous studies 12,14) . It is possible that the subjects were accustomed to the daylight or fluorescent light as a "usual" illumination so they could arrange the shades of colors on the screen more easily, while it may have been more difficult to discriminate the color-matching test of FM-100 colors under the colored illuminant because the subjects were not accustomed to environmental colored illuminant.…”
Section: Illuminant Colorssupporting
confidence: 90%
See 1 more Smart Citation
“…The findings indicated that the error scores under the red and blue illuminant were significantly higher than the error scores under white illuminant, a finding that was consistent with previous studies 12,14) . It is possible that the subjects were accustomed to the daylight or fluorescent light as a "usual" illumination so they could arrange the shades of colors on the screen more easily, while it may have been more difficult to discriminate the color-matching test of FM-100 colors under the colored illuminant because the subjects were not accustomed to environmental colored illuminant.…”
Section: Illuminant Colorssupporting
confidence: 90%
“…For example, in the control rooms of some military battlefield control towers, operators manipulate a radar system under red or blue illuminant, and operators working in the information center or main machine control room of military ships perform sonar detection tasks on the VDTs under red, blue, and white illuminant 12) . In this kind of environments, any hue discrimination errors are critical.…”
Section: Introductionmentioning
confidence: 99%
“…More accommodation is required to focus red light, and this becomes more difficult with age. Red light thus tends to produce more fatigue (Kinney et al, 1983), particularly with older people.…”
Section: Performance and Preference With Various Vdt Phosphors Sm Lmentioning
confidence: 99%
“…They require more acco •, ,t ion to focus them on the retina, which could be uncomfortable Indeed, a recent study of the eye-movements of men monitoring a sonar display for two hours under different colors of ambient light gave some evidence of greater physiological fatigue under red light than under blue or white (42 The widespread unpopularity of red light (55, 56) should not be dismissed out of hand, because it has been shown (57: 58) that there is a relationship between reports of how people feel and their physiological measures@ Liebhart has reviewed the evidence that the emotions are aroused when one believes that one has been exposed to an unpleasant stimulus (59).…”
Section: P 4onementioning
confidence: 99%